Application of the Petis Mixer Machine Equipped with Temperature Control to Increase the Effectiveness of the Production Process of the Petis Sidoarjo UKM - Purbodjati; Edy Sulistiyo (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
The problem faced by UKM Petis Sidoarjo is that the production process of petis kupang still uses human labor which is done conventionally. This causes the cooking time as well as the stirring required in one production process to be relatively long (5 hours). In the process of stirring the petis still using a wooden stick that is constantly stirred by hand, this requires extra effort so that employees are often tired, and the stove temperature is unstable, causing partners to frequently check so that the petis is not overcooked (burnt). To solve this problem, this community service program will apply a petis mixer machine. The implementation method in this activity is designing, manufacturing, assembly, machine testing, machine handover, machine operation and maintenance training, and periodic monitoring as well as financial management training and regular monitoring. The results of this activity included: accelerating the cooking process as well as stirring from 5 hours to 3 hours; employees are not exhausted during the stirring process because it is carried out by means of an electric motor; and the temperature of the stove can be controlled and adjusted as needed so that the petis is avoided from culverts and saves LPG consumption.